'Fossil Fueling the Apocalypse': Australian Coal Subsidies and the Agreement on Subsidies and Countervailing Measures. Issue 1 (12th March 2018) - SLATTERY, CHRISTIAN HARRIS
Abstract: Global fossil fuel subsidies are substantial and contribute to climate change. They also undermine the ambitions of the Paris Agreement. However, under the WTO, the international community's foremost economic institution, it is renewable energy subsidies, not fossil fuel subsidies, that have been subjected to litigation. To date, no fossil fuel subsidy has ever been brought before the WTO's Dispute Settlement Body (DSB). This paper makes a unique contribution to the literature on energy subsidies by applying the WTO covered Agreement on Subsidies and Countervailing Measures (1994) (SCM Agreement) to a specific government measure designed to support the coal export industry in Australia: namely, the proposed concessional loan for the construction of a rail line between the Carmichael coal mine and Abbot Point coal port by the Northern Australia Infrastructure Facility (NAIF). In finding that this measure is in breach of the SCM Agreement, this paper foreshadows future litigation and provides guidance to non-government organizations (NGOs) seeking to identify other unlawful fossil fuel subsidies.